GLASS SUBSTRATE WITH LIGHT DIRECTIVITY AND ILLUMINATOR EMPLOYING THE SAME - EINISHI, TOSHIHIKO; YAMASHITA, NAOTO; KAGA, NAOKO; UMEDA, HIRONORI; SUETSUGU, TATSUYA; KADONO, KOHEI (2008)
The present invention provides a high-precision planar light source with a sufficiently uniform luminance and sufficient light directivity to direct light to travel in a specific direction, using a simple production process. More specifically, the invention provides: a glass substrate with light directivity produced by applying a paste containing at least one member selected from the group consisting of lithium compounds, sodium compounds, potassium compounds, rubidium compounds, cesium compounds, copper compounds, silver compounds, and thallium compounds, an organic resin, and an organic solvent to one or both sides of a glass substrate containing an alkali metal as a glass component, and then performing heat treatment at a temperature lower than the softening temperature of the glass substrate; and a planar light source using the glass substrate.